2009
DOI: 10.1104/pp.109.147827
|View full text |Cite
|
Sign up to set email alerts
|

The Pepper 9-Lipoxygenase GeneCaLOX1Functions in Defense and Cell Death Responses to Microbial Pathogens

Abstract: Lipoxygenases (LOXs) are crucial for lipid peroxidation processes during plant defense responses to pathogen infection. A pepper (Capsicum annuum) 9-LOX gene, CaLOX1, which encodes a 9-specific lipoxygenase, was isolated from pepper leaves. Recombinant CaLOX1 protein expressed in Escherichia coli catalyzed the hydroperoxidation of linoleic acid, with a K m value of 113. 9 mM. Expression of CaLOX1 was differentially induced in pepper leaves not only during Xanthomonas campestris pv vesicatoria (Xcv) infection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
144
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 68 publications
9
144
0
1
Order By: Relevance
“…This is the case for lox1lox5 mutants, in which lack of 9-LOX activity enhances susceptibility to Pseudomonas spp. inoculation (Hwang and Hwang, 2010;López et al, 2011), even though callose production in bacterially infected leaves did not vary with respect to wild-type plants. Although callose production in bzr1-1D mutant leaves was similar, in these plants, constitutive activation of BR signaling increased resistance to Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the case for lox1lox5 mutants, in which lack of 9-LOX activity enhances susceptibility to Pseudomonas spp. inoculation (Hwang and Hwang, 2010;López et al, 2011), even though callose production in bacterially infected leaves did not vary with respect to wild-type plants. Although callose production in bzr1-1D mutant leaves was similar, in these plants, constitutive activation of BR signaling increased resistance to Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in Arabidopsis (Arabidopsis thaliana) showed a 9-LOX function in activating local defense and stomata closure against virulent Pseudomonas spp. (Hwang and Hwang, 2010;López et al, 2011;Montillet et al, 2013) as well as 9-LOX and a-DOX pathway cooperation in triggering systemic resistance (Vicente et al, 2012). There is also evidence of a role in activating systemic defense for C9 oxylipins formed by nonenzymatic free radical reactions (Jung et al, 2009;Wang et al, 2014;Wittek et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2-HOT also participates in the defense of Nicotiana attenuata against insect feeding (Gaquerel et al, 2012). In addition, 9-hydroxy-10,12,15-octadecatrienoic acid (9-HOT) was reported to antagonize the action of ethylene, triggering molecular events such as the accumulation of callose, the production of reactive oxygen species (ROS), and transcriptional changes for genes involved in plant defense (Hwang and Hwang, 2010;López et al, 2011). FAOHs also accumulate during oxidative stress, when their functions are still elusive (op den Camp et al, 2003;Montillet et al, 2004).…”
mentioning
confidence: 99%
“…vesicatoria infection. 20) 9-LOXs have been suggested to positively regulate defense and cell death responses to microbial pathogens.…”
Section: Introductionmentioning
confidence: 99%